PENERAPAN STRATEGI INFORMATION SEARCHUNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGANPADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IVSD NEGERI 010 PAGARAN TAPAH DARUSSALAM - Sri Rahayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low ability students in writing essays. This study aims to determine the increase in the ability to write about a bouquet of fourth grade students of SD Negeri 010 Pagaran Tapah Darussalam. Subjects with Strategic Information Search. The subjects were 11 students. Form of research is classroom action research. The data collection technique used is the technique of observation and tests the ability to write essays. Based on the results, it can be concluded that with menerapkaan Search Information Strategy can improve students' ability to write essays on subjects Indonesian-grade students of SD Negeri 010 Pagaran Tapah Darussalam. Before action is taken the ability to write essay students classified as